Hermite polynomials and its application in linear harmonic oscillator - Tee, An Song; Yudariah Mohammad Yusof; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2010